Effect of 5E Learning Model on Academic Achievement in Teaching Mathematics: Meta-analysis Study - et. al., Suzianah Bakri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Active student involvement in the teaching and learning process is important in helping students strengthen their understanding of a concept better. Knowledge that is not related to existing knowledge will be easily forgotten. To strengthen understanding and knowledge, students need to build new knowledge on top of existing knowledge to ensure meaningful learning will take place. The 5E learning model is optically discerned to be able to have a positive impact on the development of student achievement. This study examines the benefits of the 5E learning model approach in teaching mathematics through a systematic review of research literature published from 2013–21 producing a total of 20 interventions (20 studies) that satisfy this study's criteria. The results show that conceptual knowledge, procedural knowledge and flexibility of procedures for the implementation of greater interventions, which can improve mathematical learning when used appropriately. This study suggests that teachers may need additional support to complete the course of mathematics using the five phases of learning in the 5E model, which in turn can assist in conducting teaching in an orderly and effective manner. In this way, it is important to implement the construction of learning modules for the fundamental topics of algebra based on the 5E model.